Optimization of sulfamethazine sodium adsorption onto activated carbon-based Salix psammophila: investigation of adsorption behavior and mechanism. Issue 4 (3rd April 2019) - Liu, Xiao; Wan, Yibei; Liu, Penglei; Zhao, Lei; Zou, Weihua
Abstract: A study on the adsorption of sulfamethazine sodium (SMS) from aqueous solution onto the activated carbon (AC)-based Salix psammophila (SP) by phosphoric acid activation was conducted. The central composite design under response surface methodology was employed for the removal of SMS and the process parameters were optimized. Influence of adsorbent dose, initial concentration of SMS, contact time and solution pH on the adsorption capacity of AC was investigated. The optimum adsorption conditions were obtained using adsorbent dosage of 0.54 g/L, initial concentration of 322 mg/L, contact time of 8 hours, pH value of 4.04. Kinetic studies showed the adsorption followed a pseudo-second-order model and Elovich model. The experimental equilibrium data were fitted Koble-Corrigan model and Freundlich model well and the maximum monolayer adsorption capacity of AC calculated by Langmuir model was 338.58 mg/g at 25 °C. In addition, AC was characterized by the SEM–EDS, BET, FITR and point of zero charge (pHpzc ). The mechanisms of SMS sorption onto AC were explored. Desorption and regeneration tests were carried out to evaluate the feasibility of reusing the AC. This study indicated the AC prepared from SP was an excellent adsorbent with the low cost and high performance. Graphical Abstract: uf0001